Kriminalisasi Cyber-Retribution (Pembalasan Digital) dan Fenomena Digital Mob Justice: Komparasi Batasan Hukum Pidana Indonesia dan Korea Selatan dalam Melindungi Privacy Interest - Mudyawati, Rahmalina Nurul; Mudyawati, Melani Nurul (Faculty of Law Universitas Pattimura, 2025)
This study is motivated by the escalating phenomenon of cyber-retribution and digital mob justice, which poses a significant threat to individual privacy rights. The objective of this research is to analyze the comparative criminal law boundaries between Indonesia and South Korea regarding digital retribution and the protection of privacy interests. This research employs a normative legal method with statutory and comparative approaches. The findings reveal that Indonesian criminal law remains fragmentary, relying heavily on ambiguous defamation offenses under the Electronic Information and Transactions (ITE) Law, thus failing to protect privacy comprehensively. Conversely, South Korea demonstrates a more progressive legal framework with specific regulations explicitly targeting doxing and non-consensual content dissemination. In conclusion, Indonesia requires a reconstruction of cybercrime offenses to shift the legal paradigm from merely protecting reputation to safeguarding substantial privacy interests.